2003
DOI: 10.1159/000072378
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Iron Restriction Increases Plaque Stability in Apolipoprotein-E-Deficient Mice

Abstract: Accumulative evidence has supported the role of iron in the development of atherosclerosis. To test whether iron-mediated oxidative stress influences plaque stability, apoliporotein-E (ApoE)-deficient mice (3 months old) were placed on a chow diet or a low-iron diet for 3 months, and the abundance of interstitial collagen and the expression of the matrix degradation-associated enzyme, matrix metalloproteinase-9 (MMP-9), in vascular lesions were assessed. A low-iron diet appeared to reduce iron deposition while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…In apoE-deficient mice fed with a low-iron diet, lower expression of MMP-9 and higher collagen content in lesions were observed. 36 Oxidation of matrix macromolecules may enhance their decomposition by proteolytic enzymes. 37 Matrix degradation can be followed by lesion rupture and occlusion of the vessel.…”
Section: Discussionmentioning
confidence: 99%
“…In apoE-deficient mice fed with a low-iron diet, lower expression of MMP-9 and higher collagen content in lesions were observed. 36 Oxidation of matrix macromolecules may enhance their decomposition by proteolytic enzymes. 37 Matrix degradation can be followed by lesion rupture and occlusion of the vessel.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been shown that removal of stored iron from the body can decrease the amount of iron deposition within atherosclerotic lesions in animal studies. Depletion of lesion iron levels in vivo by phlebotomy, systemic iron chelation treatment or dietary iron restriction reduces lesion size in these studies and increases plaque stability (10,15,27). The original formulation of the iron hypothesis did not specify a mechanism.…”
Section: Discussionmentioning
confidence: 95%
“…21 The small but growing literature on the effects of induced iron depletion/deficiency in various experimental models of oxidative or inflammatory injury strongly supports beneficial effects of eliminating storage iron. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Correlation of in vitro with in vivo endothelial iron status will be assisted by future studies into the basis for an interesting phenomenon seen in human umbilical vein endothelial cells (HUVEC). Sensitivity of HUVEC to oxidative injury or high glucose levels decreases sharply with subculture in vitro after a few passages.…”
Section: See Page 1577 Endothelial Iron Status In Vivomentioning
confidence: 99%